Degradation of Bone Quality in a Transgenic Mouse Model of Alzheimer′s Disease. (1st November 2022) - LLabre, Joan E; Gil, Cristianel; Amatya, Neha; Lagalwar, Sarita; Possidente, Bernard; Vashishth, Deepak
ABSTRACT: Alzheimer′s disease (AD) patients present with symptoms such as impairment of insulin signaling, chronic inflammation, and oxidative stress. Furthermore, there are comorbidities associated with AD progression. For example, osteoporosis is common with AD wherein patients exhibit reduced mineralization and a risk for fragility fractures. However, there is a lack of understanding on the effects of AD on bone beyond loss of bone density. To this end, we investigated the effects of AD on bone quality using the 5XFAD transgenic mouse model in which 12‐month‐old 5XFAD mice showed accumulation of amyloid‐beta (Aβ42) compared with wild‐type (WT) littermates ( n = 10/group; 50% female, 50% male). Here, we observed changes in cortical bone but not in cancellous bone quality. Both bone mass and bone quality, measured in femoral samples using imaging (micro‐CT, confocal Raman spectroscopy, X‐ray diffraction [XRD]), mechanical (fracture tests), and chemical analyses (biochemical assays), were altered in the 5XFAD mice compared with WT. Micro‐CT results showed 5XFAD mice had lower volumetric bone mineral density (BMD) and increased endocortical bone loss. XRD results showed decreased mineralization with smaller mineral crystals. Bone matrix compositional properties, from Raman, showed decreased crystallinity along with higher accumulation of glycoxidation products and glycation products, measured biochemically. 5XFAD mice also demonstrated loss of initiation and maximum toughness. We observed that carboxymethyl‐lysine (CML) and mineralization correlated with initiation toughness, whereas crystal size and pentosidine (PEN) correlated with maximum toughness, suggesting bone matrix changes predominated by advanced glycation end products (AGEs) and altered/poor mineral quality explained loss of fracture toughness. Our findings highlight two pathways to skeletal fragility in AD through alteration of bone quality: (i) accumulation of AGEs; and (ii) loss of crystallinity, decreased crystal size, and loss of mineralization. We observed that the accumulation of amyloidosis in brain correlated with an increase in several AGEs, consistent with a mechanistic link between elevated Aβ42 levels in the brain and AGE accumulation in bone. © 2022 American Society for Bone and Mineral Research (ASBMR).